Influence of Atomic Doping on Thermal Stability of Ferrite Nanoparticles—Structural and Magnetic Studies - Klekotka, Urszula (Materials (Basel), 2020)
In this paper, a series of experiments are reported where ferrite nanoparticles were synthesized with different substitution percentages (5, 10, 15, or 20%) of Fe(2+) by Co(2+), Mn(2+), or Ni(2+) ions. Afterwards, the prepared nanoparticles were thermally treated between 50 and 500 °C in air for 24 h in order to observe how doping influences the oxidation process induced by temperature elevation and access to O(2). Nanoparticles were imaged before and after thermal treatment by transmission electron microscopy and were analyzed by X-ray diffraction, vibrating sample magnetometry, and Mössbauer spectroscopy. Presented studies reveal that the amount and kind of doped transition metals (of replaced Fe(2+)) strongly affect the oxidation process of ferrite nanoparticles, which can govern the application possibility. Each transition element suppresses the oxidation process in comparison to pure Fe-oxides, with the highest impact seen with Ni(2+).